ESSENCE OF THE PROBLEMS OF PERFORMANCE MANAGEMENT OF PROFESSIONAL SERVICE ACTIVITIES OF CIVIL SERVANTS AT THE STAGE OF RECRUITMENT AND SELECTION - D. Simutova (Вестник университета, 2019)
The problems of managing the effectiveness of professional service activities of civil servants, expressed in the lack of professionalism and competence of employees, have been investigated. The problems that arise at the stage of attracting personnel to the civil service of the Russian Federation have been considered from the point of view of the established qualification requirements for civil service positions. The cause of the problems at the selection stage has been disclosed in the practice of using methods for evaluating candidates for positions in the civil service.